Tensile Behaviour and Morphology of Polypropylene/Polycar-bonate/Polypropylene-graft-maleic Anhydride Blends - Mat-Shayuti, M.S. (EDP Sciences, 2017)
This work investigates the effect of blending polycarbonate (PC) into polypropylene (PP) matrix polymer on mechanical tensile properties and morphology. The blends, containing 5 to 35 of polycarbonate and 5 compatibilizer, were compounded using twin-screw extruder and fabricated into standard tests samples using injection molding. The compatibilizer used was polypropylene-graft-maleic anhydride (PP-g-MA). The values of tensile strengths and moduli for PP/PC/PP-g-MA blends were lower than that of pure PP. Tensile strength of pure PP was 37.74 MPa, whereas the highest tensile strength among the blends was 32.60 MPa at 70/25/5 composition. The pattern for the blends is non-linear, where the optimum amount of PC for tensile strength was 25. Addition of PP-g-MA imparts positive effect towards the blends, shown by higher value for both tensile strength and tensile modulus compared to the noncompatibilized blend. Microscopy analysis showed PC reinforcement phase existed as particulates dispersed in PP matrix phase. PC particulates size depends on its fraction and compatibilizer content. As PC content in compatibilized blends increases, its particulate size also increases. © 2017 The Authors, published by EDP Sciences.